(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This article analyzes the fundamental components of pedagogical mastery and their strategic role in the activities of a modern pedagogical physician. The study highlights the development mechanisms of medical education technologies, specifically the integration of digital transformation, artificial intelligence, and simulation learning methods. The results of the article will serve to improve the quality of education in medical universities and improve the methodology for training competitive personnel. The article is dedicated to one of the most pressing issues of modern medical education - the professional skills of teachers in higher medical educational institutions and the evolutionary development of educational technologies.